Cutting tool geometries - Bollinger, Steven; Cook, Jerome T.; Mason, Frederick (Fundamental manufacturing processes)
This program examines single point turning tool and toolholder geometries, milling and multi-point tool geometries and chipbreakers and the formation of chips.